2020
DOI: 10.3390/w12051426
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the Potential Impacts of Projected Climate Change on Streamflow in the Vakhsh River Basin in Central Asia under CMIP5 RCP Scenarios

Abstract: Millions of people in Uzbekistan, Turkmenistan, Tajikistan, and Kyrgyzstan are dependent on the freshwater supply of the Vakhsh River system. Sustainable management of the water resources of the Vakhsh River Basin (VRB) requires comprehensive assessment regarding future climate change and its implications for streamflow. In this study, we assessed the potential impacts of projected climate change scenarios on the streamflow in the VRB for two future periods (2022–2060 and 2061–2099). The probable changes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 92 publications
3
7
0
Order By: Relevance
“…In addition, studies investigating the impacts of current and future climate extremes (Lins and Slack 2005;Milly et al 2002;Sharma et al 2018) indicate that the U.S. population is becoming alarmingly vulnerable to flood-associated risks (Naz et al 2016;Wing et al 2018). These trends are particular not only to CONUS but have been observed in other parts of the world, including Europe (Jarosińska and Pierzga 2017;Teuling et al 2019), Central Asia (Gulakhmadov et al 2020) and South America (Lara et al 2017). Under various growth scenarios for future climate as prescribed by global climate models, and, despite local-and regional-scale complexities, this continual, upward intensification of median and high flows remains a consistent find in these studies.…”
Section: Introductionsupporting
confidence: 74%
“…In addition, studies investigating the impacts of current and future climate extremes (Lins and Slack 2005;Milly et al 2002;Sharma et al 2018) indicate that the U.S. population is becoming alarmingly vulnerable to flood-associated risks (Naz et al 2016;Wing et al 2018). These trends are particular not only to CONUS but have been observed in other parts of the world, including Europe (Jarosińska and Pierzga 2017;Teuling et al 2019), Central Asia (Gulakhmadov et al 2020) and South America (Lara et al 2017). Under various growth scenarios for future climate as prescribed by global climate models, and, despite local-and regional-scale complexities, this continual, upward intensification of median and high flows remains a consistent find in these studies.…”
Section: Introductionsupporting
confidence: 74%
“…Our result of the trend analysis showed that annual runoff significantly increased in upstream and downstream areas of the KRB. In our previous study, we predicted a significant upward trend in the high flow of the Vakhsh River [32], which is adjacent to the Kofarnikhon River in Tajikistan. The upward trend in river runoff can be explained by the rapid melting of snow and ice caused by the constant rise in air temperature.…”
Section: Discussionmentioning
confidence: 86%
“…In recent years, due to the variations in water resources and the frequent reoccurrence of natural disasters, studies estimating the hydrological response to climate variability and Our previous study in which the SWAT model was applied in the mountainous Vakhsh River Basin (VRB) in Central Asia [32] showed that the hydrologic response to climate variations had significant effects on runoff changes. It was found that global warming accelerated the process of snow/glacier melting, which induced an increasing runoff in the VRB in the past recent decades [32]. In this study, the variability in runoff to climate change and anthropogenic disturbances were separated, which significantly varied from basin to basin [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…As in our previous study, Gulakhmadov et al presented the hydrological model calibration results they obtained with the SWAT-CUP tool before and after the EB approach. The application of EB had a positive impact on the modeling of river flow in a mountain watershed [61].…”
Section: Methodsmentioning
confidence: 99%